2023
DOI: 10.1108/lodj-10-2021-0441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of managerial skills and ties on business model innovation: the role of exploitative and explorative learning

Abstract: PurposeResearch in the area of business model innovation (BMI) has focused on theoretical and exploratory discussions, thereby creating a lack of empirical evidence on the role of top management in BMI. The current study focuses on this research gap and provides empirical evidence by studying the impact of top managers’ managerial skills, managerial ties and entrepreneurial skills on BMI. It also seeks to explore the mediating influence of explorative and exploitative learning.Design/methodology/approachData w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 111 publications
1
7
0
Order By: Relevance
“…Exploitative learning can help organizations effectively respond to environmental dynamics by adapting technology as a basis for improving business performance. Previous research conducted by Bashir et al (2023) found that exploitative learning has a correlation in improving business performance. Thus, the first hypothesis is proposed as follows:…”
Section: Literature Review Exploitative Learningmentioning
confidence: 91%
See 1 more Smart Citation
“…Exploitative learning can help organizations effectively respond to environmental dynamics by adapting technology as a basis for improving business performance. Previous research conducted by Bashir et al (2023) found that exploitative learning has a correlation in improving business performance. Thus, the first hypothesis is proposed as follows:…”
Section: Literature Review Exploitative Learningmentioning
confidence: 91%
“…Acquiring current skills and knowledge in business processes and innovation is a major focus on exploitative learning (Bashir et al, 2023;Zhang et al, 2023). According to Bashir et al (2023) exploitative learning encourages organizations to be oriented towards innovation which results in organizational performance. During the exploitation phase, learning and experience become very important in improving organizational performance.…”
Section: Literature Review Exploitative Learningmentioning
confidence: 99%
“…Similarly, Anwar and Ali Shah (2020) point out that new ventures establish network collaboration with external partners (customers, suppliers and industrial partners) to obtain the essential resources to innovate their BM and reap novel opportunities in turbulent markets. In a similar vein, Bashir et al (2023b) found that managers' human skills and social ties significantly impact the firm's ability to actively innovate their BM to maximize the firm value. Researchers have also demonstrated that IC dimensions promote new product development (Chen et al, 2014).…”
Section: 43mentioning
confidence: 88%
“…Wang et al. (2023) and Bashir et al . (2023) pointed out that network ties as the critical sources for start-ups to gain and use these resources are the external trigger for BMI.…”
Section: Introductionmentioning
confidence: 92%
“…For example, Dymitrowski and Mielcarek (2023) indicated that the impact of external networks on BMI is undoubtedly worth exploring. and Bashir et al (2023) pointed out that network ties as the critical sources for start-ups to gain and use these resources are the external trigger for BMI. Similarly, Yi et al (2022) argued that BMI should be considered a firm's purposely constructed collaboration network.…”
Section: Introductionmentioning
confidence: 99%